Wall Pressure Signatures of Turbulent Flow Over Longitudinal - Abdulbari, Hayder A.; Mahammed, Hassan D.; Zulkefli, Yaacob; Wafaa, Kamil Mahmood (EDP Sciences, 2016)
Five triangular riblets longitudinal in the streamwise direction have been studied experimentally. The riblets have pick to pick spaced (s) equal to 1000 μm and with groove height to space ratio (h/s) 0.4, 0.6, 0.8 and 1. The tests were conducted in a full turbulence water channel on a flat plate for Reynolds numbers 13000 to 53000 based on channel hydraulic diameter. Pressure drop was measured using pressure transmitter gauge with pressure tap points of 12.7 mm in diameter were provided at the bottom of the channel. The main purpose of the present study is to investigate the response of turbulent flow to longitudinal grooves of triangular shaped riblets and compare the effect of the turbulence structure over smoothed and grooved surfaces with pressure drop measurements. 10.20 was the maximum drag reduction appear at h/s equal to (1).